THE RELATIONSHIP OF FAMILY SUPPORT WITH THE LEVEL OF ANXIETY OF PREGNANT WOMEN BEFORE DELIVERY - Debby Yolanda; Kricillia Molly Morita (Jurnal Endurance, 2025)
Anxiety during the 1st stage of labor is caused by fear of giving birth, fear of increasing pain, fear of damage or deformity to the body such as episiotomy, suture rupture or caesarean section, and the mother is afraid of injuring her baby. The aim of this research is to determine the relationship between family support and the level of anxiety of pregnant women before giving birth in BPM Padang Panjang City. This type of research is descriptive analytic with a cross-sectional study design. The research sample was 40 respondents. Analysis with chis-quare test. with a confidence level of 95%. The results of the study showed that more than half of the respondents received family support during childbirth, namely 22 (55.0%), more than half of the respondents were not worried about giving birth, namely 17 (42.5%). There is a significant relationship between family support and maternal anxiety facing childbirth with a p value of 0.002 and an OR value of 11.700. It was concluded that there was a relationship between family support and the level of anxiety facing childbirth. To midwives to reduce the anxiety of pregnant women in the third trimester in facing childbirth by providing health education before taking action and improving the quality of midwifery services and increasing effectiveness in providing midwifery care to birthing patients